Assessment of Functional Literacy Needs and Enrichment Interests of Commercial Drivers in North-Central Nigeria - YUSUF, Imran; LAWAL, Raheem Adebayo (Ilorin Journal of Education, 2025)
Literacy, being a component of education, is supposed to empower individuals with knowledge, attitudes, skills and values for personal, interpersonal and community development. Individuals employ the attributes in a bid to obtain information, values and other skills for proper functioning. Therefore, functional literacy needs and enrichment interests among commercial drivers in North-central Nigeria were evaluated by this study. The descriptive research survey was employed in this study. The population under study was all literate commercial drivers and the study target population consisted of all inter-state literate commercial drivers of the three North-central Nigerian states. Six hundred and sixty respondents were sampled using the random sampling method. Data from the respondents were gathered with the help of a researcher-crafted questionnaire. Three-week interval test-retest process was utilized in order to find out the reliability of the tool and a score of 0.87 was found. It was discovered that the commercial drivers required functional literacy to a great extent for cultural (x ̅=3.30), civic (x ̅=3.25), economic (x ̅=3.38) and social (x ̅=3.31) development in every environment; they were moderately interested in developing their prose (x ̅=3.12), document (x ̅=3.18) and quantitative (x ̅=3.28) literacy domains. The inference of these findings was that planning and organizational functional literacy programs for the drivers, especially for economic development and quantitative domain, were called for. The research implied that there should be an organized functional literacy program for the commercial drivers, taking into consideration their economic development and quantitative literacy